2009
DOI: 10.1134/s1087659609010039
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron study of lanthanide borosilicate glass

Abstract: The elemental and ionic quantitative analyses of the synthetic lanthanide borosilicate glass (Al-B-Gd-Hf-La-Nd-Pu-Si-Sr-O) are performed using the characteristics of the X-ray photoelectron spectra of the outer-shell and inner-shell electrons in the binding energy range 0-1000 eV. The oxidation states of the metal ions in this glass are determined and correspond to the Al 3+ , La 3+ , Nd 3+ , Gd 3+ , Hf 4+ , Pu 4+ , Si 4+ , and Sr 2+ ions. Taking into account the binding energies of the O 1 s electrons for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Computer simulation of experimental XANES spectrum of Pu L III edge in the glass studied provided the best fit when ~90% of total Pu existed as Pu(IV) and ~10% was present as Pu(III). This result was in a good agreement with reference data [2,14] and our XPS data [8], where almost all Pu was found to be in a tetravalent state. Magnitude of the Fourier transform (FT) of EXAFS spectrum at Pu L III edge shows that the peak due to first coordination sphere is much more intense than that of the second shell (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Computer simulation of experimental XANES spectrum of Pu L III edge in the glass studied provided the best fit when ~90% of total Pu existed as Pu(IV) and ~10% was present as Pu(III). This result was in a good agreement with reference data [2,14] and our XPS data [8], where almost all Pu was found to be in a tetravalent state. Magnitude of the Fourier transform (FT) of EXAFS spectrum at Pu L III edge shows that the peak due to first coordination sphere is much more intense than that of the second shell (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The as-prepared glasses contained undissolved PuO 2 and those thermally-heated at 1250 C -PuO 2 -HfO 2 solid solution. In our previous work we have found that Pu in the LaBS glass is predominantly tetravalent [8]. The present work extends our investigations on determination of local environment of Pu and its analogue -Hf in the LaBS glass using X-ray absorption fine structure (XAFS) spectroscopy.…”
Section: Introductionsupporting
confidence: 77%
“…The as-prepared glass contained minor britholite structure phase and traces of PuO 2 or/and PuO 2 -HfO 2 solid solution [6,8]. No appreciable changes in phase composition and texture of the glass were found after ~3 yrs of storage.…”
Section: Glass #1mentioning
confidence: 99%
“…Conventional borosilicate glasses have Pu solubilities in amounts of only up to ~2 wt.% [5]. In our previous works [6][7][8][9][10] we described the structure of the LaBS glasses both as-prepared and stored for a period of up to 2 years. The glasses had a tendency to devitrification with increase of storage time.…”
Section: Introductionmentioning
confidence: 99%
“…Stefanovsky and coworkers examined a Pu-bearing LaBS Frit X glass containing 9.5 wt % PuO 2 (Stefanovsky, 2007, Maslakov, 2009. In these studies, EXAFS, XANES, x-ray photoelectron spectroscopy (XPS) and infrared (IR) spectroscopy were used to determine the valence state and local structure of the glass.…”
Section: Local Environment Of Pu In Glassmentioning
confidence: 99%